The strange fate of Brexit and Grexit and the Eurozone: Integration and disintegration - Heti Suryani Fitri Sulaeman; Sri Mulyantini Moelyono; Jubaedah Nawir (Contemporary Economics, 2019)
This article addresses an anomaly in the European Union (EU)'s recent evolution. Two years ago, Great Britain's exit from the EU seemed improbable, while Greece's departure appeared to be imminent. The outcome was precisely the reverse. We explain the paradox and examine its ramifications. The principal finding is that Brexit should be less disruptive than initially supposed if the EU responds constructively by filling the gaps in its institutional setup that reduce the system's vulnerability to asymmetric shocks. Greece's decision to remain enhances the prospects for Eurozone reform.
Keywords: F36; H63; H77; P11; 330; Brexit; Grexit; Eurozone